Unravelling the interplay: brain regional atrophy and neuropsychological function in early Alzheimer’s disease - Heo, Doyun; Kim, Min-Seong; Lee, Yun-Jin; Kim, Seon-Kyeong; Kim, Yong Sung; Sung, Wonjae; Kim, Hee-Jin (Frontiers in Aging Neuroscience, 2025)
ObjectivesThe structural changes in the brain differ between normal aging and Alzheimer’s dementia (AD). The results of cognitive function tests reflect structural changes in the brain in AD. This study aimed to determine the specific relationship between regional brain volume and neuropsychological subtest scores.MethodsNinety-three patients with definitive diagnosis of AD (confirmed by PET) were retrospectively enrolled. An automated program Quick Brain Volumetry (QBraVo) was used to measure the regional gray matter (GM) volume of the participants. Each score of the Seoul Neuropsychological Screening Battery (SNSB) subset test was statistically analyzed to observe correlations between regional brain volumes and cognitive function. Results of the SNSB subset test were compared to the degree of brain volume atrophy.ResultsThe Controlled Oral Word Association Test (COWAT), Trail making test for the elderly (TMT–e), and Korean version Boston naming test (K-BNT) were strongly correlated with GM volume atrophy, mainly in the temporal lobe. Memory functions, including Seoul verbal learning test (SVLT), Rey complex figure test (RCFT) recall and recognition tests, were significantly correlated with both the temporal and frontal regions. Various tests reflecting frontal and executive functions did not reveal significant correlations with the frontal regions. The BNT test scores reflecting language function did not correlate with frontal atrophy. Tests reflecting visuospatial capability (RCFT) were also related to inferior frontal and temporal atrophies.ConclusionIn patients with AD, the results of most cognitive function tests are related to the degree of atrophy of the temporal and frontal cortices. Further research is necessary to determine the extent to which cognitive function test results are associated with brain atrophy.